Path-dependent Routines in the Evaluation of Novelty: The Effects of Innovators$1 (BNew Knowledge Use on Brokerage Firms$1 (BCoverages - Theeke, Matt; Polidoro, Francisco; Fredrickson, James W. (2018)
This paper examines how path dependencies in evaluation routines affect a brokerage firm$1 (Bs decision to provide coverage to a company that builds on new knowledge. Companies depend on brokerage firms to gain access to external resources, as a brokerage firm$1 (Bs coverage is a valuable form of recognition that may lower a company$1 (Bs cost of capital and increase its value. Yet path dependencies in a brokerage firm$1 (Bs evaluation routines may make it less likely to cover a company whose inventive activities build on different knowledge than it used in the past. Using data on 183 U.S. publicly traded medical device companies from 1993 to 2006, we examine how a company$1 (Bs use of new knowledge affects a brokerage firm$1 (Bs decision to cover the company. Our results suggest that a company may face a tension between exploration and resource dependence, as after it overcomes internal path dependencies that hinder exploration and successfully uses new knowledge, it may still fail to gain the attention of outside organizations on which it depends to access relevant resources due to externally borne path dependencies in the routines these outside organizations use to evaluate novelty. Also, in contrast with existing literature suggesting that brokerage firms have homogenous expectations for which strategies are appropriate for different types of companies, our results highlight that brokerage firms differ in how they respond to companies$1 (Binventive activities based on factors such as their prior exposure to new knowledge, prior evaluation of the companies$1 (Bdownstream product markets, and scope of technological expertise. - Reproduced.s
Keywords: Innovation; Brokerage firms